Carbonic Anhydrases : Biochemistry and Pharmacology of an Evergreen Pharmaceutical Target - Supuran, Claudiu T., 1962-; Nocentini, Alessio (Academic Press, 2019)
Carbonic Anhydrases provides an interdisciplinary review of the burgeoning carbonic anhydrase (CA) research area, spanning from CAs classification (biochemical and structural features) to drug design and pharmacology of CA inhibitors and activators, finally touching on the biotechnological applications of these metalloenzymes. The book adopts a clear step-by-step approach and introduction to this intricate and highly interdisciplinary field. A diverse range of chapters from international experts speak to CA classification and distribution, the mechanisms of action and drug design of inhibitors and activators, the druggability of the various isoforms in the treatment of a multitude of diseases, and threats to human health. Carbonic Anhydrases provides biology, biochemistry, and medicinal chemistry students and researchers a thorough discussion and update on the evergreen and expanding research area of CAs.